Propionibacterium freudenreichii component 1.4-dihydroxy-2-naphthoic acid (DHNA) attenuates dextran sodium sulphate induced colitis by modulation of bacterial flora and lymphocyte homing. Issue 5 (18th November 2005) - Okada, Y; Tsuzuki, Y; Miyazaki, J; Matsuzaki, K; Hokari, R; Komoto, S; Kato, S; Kawaguchi, A; Nagao, S; Itoh, K; Watanabe, T; Miura, S
Abstract : Background and aim: 1.4-Dihydroxy-2-naphthoic acid (DHNA), a bifidogenic growth stimulator from Propionibacterium freudenreichii, is thought to have a beneficial effect as a prebiotic; however, its in vivo effect on intestinal inflammation remains unknown. The aim of this study was to determine whether oral administration of DHNA can ameliorate dextran sodium sulphate (DSS) induced colitis and to determine the possible underlying mechanisms. Method: Colitis was induced in mice by treatment with 2.0% DSS for seven days. DHNA (0.6 or 2.0 mg/kg) was given in drinking water prior to (preventive study) or after (therapeutic study) DSS administration. Colonic damage was histologically scored, and mucosal addressin cell adhesion molecule 1 (MAdCAM-1) expression and β7 positive cell infiltration were determined by immunohistochemistry. mRNA levels of proinflammatory cytokines (interleukin (IL)-1β, IL-6 and tumour necrosis factor α (TNF-α)) were determined by quantitative real time polymerase chain reaction. In addition, bacterial flora in the caecum, concentrations of short chain acids, and luminal pH were examined. Results: DHNA improved survival rate and histological damage score in mice administered DSS in both the preventive and therapeutic studies. DHNA significantly attenuated the enhanced expression of MAdCAM-1, the increased β7 positive cell number, and the increased mRNA levels of IL-1β, IL-6, and TNF-α in DSS treated colon. In addition, the decreased number of Lactobacillus and Enterobacteriaceae induced by DSS was recovered by DHNA. Preventive effects on decrease in butyrate concentration and decrease in pH level in mice administered DSS were also observed in the DHNA preventive study. Conclusion: DHNA, a novel type of prebiotic, attenuates colonic inflammation not only by balancing intestinal bacterial flora but also by suppressing lymphocyte infiltration through reduction of MAdCAM-1.